1972
DOI: 10.1136/bjo.56.6.447
|View full text |Cite
|
Sign up to set email alerts
|

Systemic blood pressure in open-angle glaucoma, low tension glaucoma, and the normal eye.

Abstract: The object of the present study was to investigate the hypothesis that a low systemic blood pressure might be associated with so-called low tension glaucoma: the rather unexpected result was an association between open-angle glaucoma and vascular hypertension. Theoretically, the pressure in the ophthalmic artery as shown by ophthalmodynamometry is likely to be a better index of blood pressure in arteries in the eyeball than the systemic blood pressure measured at the upper arm; however, in practice, we have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
3

Year Published

1977
1977
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(63 citation statements)
references
References 9 publications
2
57
1
3
Order By: Relevance
“…The NTG patients had a slightly higher IOP and more evident fluctuations if compared with the normal subjects. Other authors have already reported a difference in IOP between normal subjects and NTG patients [8, 9]. …”
Section: Discussionmentioning
confidence: 96%
“…The NTG patients had a slightly higher IOP and more evident fluctuations if compared with the normal subjects. Other authors have already reported a difference in IOP between normal subjects and NTG patients [8, 9]. …”
Section: Discussionmentioning
confidence: 96%
“…13 A correlation has also been reported between the occurrence of hypertension and glaucoma. 16 Watson and Greenwood 17 and Gafter et al 18 reported slightly elevated arterial pressure and low IOP in azotemic patients that did not change with hemodialysis. Low IOP has also been reported in azotemic dogs; blood pressure was not measured.…”
Section: Discussionmentioning
confidence: 97%
“…Strong associations with low diastolic blood pressure (Drance et al 1981;Morgan & Drance 1975;Richler et al 1982) and also systemic hypertension (Dielemans et al 1995;Leighton & Philips 1972;Nagin & Schwartz 1985;Wilson et al 1987) has been reported in glaucoma patients. Some authors postulated that physiologic nocturnal hypotension, in the presence of other vascular risk factors, may reduce the optic nerve head blood flow below a critical level, and thereby may play a role in the pathogenesis of anterior ischemic optic neuropathy and glaucoma (Graham et al 1995;Hayreh et al 1994).…”
Section: Discussionmentioning
confidence: 99%